2012
DOI: 10.1007/s11695-012-0597-0
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Place for Pigtail Drains in the Management of Gastric Leaks After Laparoscopic Sleeve Gastrectomy?

Abstract: Laparoscopic sleeve gastrectomy (LSG) has a specific morbidity profile in which gastric leak (GL) is the main complication. With a view to defining a standardized protocol for GL management, the present retrospective study sought to describe the clinical patterns of post-LSG GL and treatment of the latter in our university medical center. From July 2004 to December 2010, 25 patients were included. GL was described in terms of clinical presentation, time to onset, and location in the staple line. Treatment of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 37 publications
3
66
1
8
Order By: Relevance
“…However, theyreported that 26.9% of the patients examined needed additional endoscopic treatment and that only 2 out of 4 patients with antral leaks were treated. Inspired by the success of endoscopic internal drainage for the management of pseudocysts in chronic pancreatitis, Pequignot et al became the first researchers to explore the use of DPC for GL management after LSG [3]. In a study of the efficacy of endoscopic internal drainage coupled with enteral nutrition via nasojejunal catheter,Donatelli et alreported a 95.2% success rate (20/21 patients)in GL management after LSG [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, theyreported that 26.9% of the patients examined needed additional endoscopic treatment and that only 2 out of 4 patients with antral leaks were treated. Inspired by the success of endoscopic internal drainage for the management of pseudocysts in chronic pancreatitis, Pequignot et al became the first researchers to explore the use of DPC for GL management after LSG [3]. In a study of the efficacy of endoscopic internal drainage coupled with enteral nutrition via nasojejunal catheter,Donatelli et alreported a 95.2% success rate (20/21 patients)in GL management after LSG [9].…”
Section: Discussionmentioning
confidence: 99%
“…Management of GL frequently requires use of internal drainage catheters accompanied by self-expandable metal stents (SEMS) [1]. Recently, endoscopic internal drainage by double pigtail catheter (DPC) has become a recommended approach after several studies found it to be better tolerated as well as requiring fewer procedures and a shorter healing time compared to endoscopic internal drainage by SEMS [1,3]. In this report we describe our treatment of a patient who experienced distal GL after undergoing LSG using DPC.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible bias was the long study period. In our institution, we started to use double pigtail stents (DPSs) in 2009 [6]. The first patients included in the LSG-control group were treated in 2010, which gave us some time to familiarize ourselves with use of the DPS.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of early-onset or poorly tolerated GF, revisional surgery is necessary [5]. Furthermore, an endoscopic procedure can be performed as the first-line treatment of well-tolerated, delayed-onset GF [6]. When combined with surgical or endoscopic procedures, pharmacological and nutritional care consists of the administration of proton pump inhibitors, appropriate antibiotics, and nutritional support (parenteral nutrition or enteral nutrition via a feeding jejunostomy or a nasojejunal tube).…”
Section: Introductionmentioning
confidence: 99%
“…El tratamiento de fístula gástrica requiere cuidado intensivo e involucra cirujanos, radiólogos y endoscopistas (17). En un 80% de los casos de fístulas gástricas se requiere cirugía de revisión y un promedio de cinco procedimientos endoscópicos (18). En pacientes con inestabilidad hemodinámica se debe realizar un lavado de cavidad abdominal de inmediato y colocación de drenajes para luego una reintervención quirúrgica más invasiva como Y de Roux o gastrectomía total (11) (17).…”
Section: Discussionunclassified